Correlation between Systemic Inflammation and Morphological Changes of Retinal Neurovascular Unit in Patients with Early Signs of Diabetic Retinopathy: An OCT and OCT-Angiography Study - Hanli Guo; Wenjie Wu; Yue Huang; Yulong Huang; Ningxuan Jin; Huazhi Ma; Qiong Li (Ophthalmic Research)
Introduction: The aim of the study was to investigate the correlation between systemic inflammation biomarkers and morphological changes of retinal neurovascular unit (RNVU) under optical coherence tomography (OCT) and OCT angiography (OCTA) in type 2 diabetic patients with early signs of diabetic retinopathy (DR). Methods: This cross-sectional study was carried out among 93 type 2 diabetic patients with early signs of DR (170 eyes), ranging from level 10 to level 35 based on ETDRS DR severity scale score. Age-, sex-, and axial length-matched normal subjects were enrolled as controls. Systemic inflammation biomarkers including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and systemic immune-inflammatory index (SII) were calculated based on peripheral blood results. Retinal neuronal changes of RNVU were identified by accessing the thickness of macular retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) using OCT. Retinal microvascular alterations of RNVU were evaluated by measuring macular vessel density (VD) and size of foveal avascular zone (FAZ) using OCTA. Results: GCL thickness was significantly correlated with NLR (r = −0.183, p = 0.017) and MLR (r = −0.235, p = 0.002), RNFL thickness was significantly associated with MLR (r = −0.210, p = 0.008), FAZp was positively correlated with NLR (r = 0.153, p = 0.046) and MLR (r = 0.187, p = 0.014), FAZa was positively correlated with MLR (r = 0.189, p = 0.014), and VD was significantly correlated with NLR (r = −0.188, p = 0.014) on spearman correlation analysis. Additionally, VD was independently associated with SII in both univariable and multivariable GLM analysis (p < 0.05). This difference still remained statistically significant during subgroup analysis after controlling DM duration. Conclusion: Systemic inflammation biomarkers including NLR, MLR, and SII are significantly associated with not only retinal microvascular alterations but also retinal neuronal changes, providing evidence that systemic inflammation may play a crucial role on the early morphological changes of RNVU and early DR pathogenesis. SII is independently associated with VD, which supports SII may serve as a potential biomarker for monitoring early microvascular changes of DR.